Smitten by giraffe : my life as a citizen scientist - Dagg, Anne Innis (Footprints (Cheltenham, England), 2016)
"When Anne Innis saw her first giraffe at the age of three, she was smitten. She knew she had to learn more about this marvelous animal. Twenty years later, now a trained zoologist, she set off alone to Africa to study the behavior of giraffe in the wild. Years later, Jane Goodall and Dian Fossey would be driven by a similar devotion to study the behavior of wild apes. In Smitten by Giraffe the noted feminist reflects on her scientific work as well as the leading role she has played in numerous activist campaigns. On returning home to Canada, Anne married physicist Ian Dagg, had three children, published a number of scientific papers, taught at several local universities, and in 1967 earned her PhD in biology at the University of Waterloo. Dagg was continually frustrated in her efforts to secure a position as a regular professor despite her many publications and very good teaching record. Finally she opted instead to pursue her research as an independent "citizen scientist," while working part time as an academic advisor. Dagg would spend many years fighting against the marginalization of women in the arts and sciences."--